2020
DOI: 10.3389/fmolb.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Target Treatment in BRAF Mutated Melanoma

Abstract: Incidence of melanoma has been constantly growing during the last decades. Although most of the new diagnoses are represented by thin melanomas, the number of melanoma-related deaths in 2018 was 60,712 worldwide ( Global Cancer Observatory, 2019 ). Until 2011, no systemic therapy showed to improve survival in patients with advanced or metastatic melanoma. At that time, standard of care was chemotherapy, with very limited results. The identification of BRAF V600 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 84 publications
0
62
0
Order By: Relevance
“…Genetic changes to key molecules in the NRAS/BRAF/MEK pathway lead to reactivation of the previously blocked MAPK pathways or activation of alternative signaling pathways, such as the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway ( Figure 1 ) [ 11 , 36 , 75 , 76 , 77 , 78 ]. In some patients with BRAF inhibitor resistance, the activation of PI3K/AKT is driven by loss of phosphatase and tensin homolog (PTEN) expression [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic changes to key molecules in the NRAS/BRAF/MEK pathway lead to reactivation of the previously blocked MAPK pathways or activation of alternative signaling pathways, such as the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway ( Figure 1 ) [ 11 , 36 , 75 , 76 , 77 , 78 ]. In some patients with BRAF inhibitor resistance, the activation of PI3K/AKT is driven by loss of phosphatase and tensin homolog (PTEN) expression [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“… The MAPK signaling pathway ( A ) in a BRAF inhibitor-sensitive cell showing sites of action of BRAF inhibitors and MEK inhibitors, and ( B ) after BRAF inhibitor resistance development [ 78 ]. Mechanisms of resistance are numbered: (1) upregulation of RTK; (2) BRAF amplification; (3) BRAF alternative splicing; (4) loss of NF1; (6) ERK activation; (7) loss of PTEN; and (8) activation of alternative signaling pathways.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, mainly because of primary and acquired resistance to treatments, the majority of patients will ultimately relapse, and only patients harboring a BRAF mutation, observed in about 50% of cutaneous melanoma, can receive a targeted treatment with BRAF and MEK inhibitors (Spagnolo et al, 2015). The current state of molecular-target drugs and the current therapeutic scenario for patients with BRAF mutated melanoma, from the introduction of BRAF inhibitors as single agents to modern clinical practice, has been extensively described in a related minireview (Tanda et al, 2020). With the purpose of further improving the prognosis of melanoma patients, several preclinical and clinical trials are studying new actionable mechanisms and/or molecules, to simultaneously tackle multiple resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, analyses of a large cohort of melanoma patients demonstrated that ShcD is a prognostic factor in melanoma. Notably, ShcD silencing sensitizes BRAF-mutant melanoma cells to targeted therapy [ 22 , 23 ], suggesting that the regulation of ShcD expression influences both the cell motility and drug sensitivity of melanoma cells.…”
Section: Introductionmentioning
confidence: 99%